Συγκατοικώντας μὲ τὴν ἄλλη πλευρὰ τῆς Ἀνταλλαγῆς τῶν Πληθυσμῶν: Ἡ συμβίωση Χριστιανῶν προσφύγων καὶ Μουσουλμάνων ἀνταλλαξίμων στὴν Ἑλλάδα τὴν περίοδο 1914-1924 - Γκλαβίνας Γιάννης (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
The Population Exchange, the events that led to the signing of the Lausanne Convention and the resettlement of hundreds of thousands of refugees who fled to Greece after 1922 mark in many respects a defining milestone for modern Greek history. The magnitude of the Asia Minor Catastrophe and the trauma caused by the events of 1922-1923 to the Greek national identity normally resulted in the collective perception of the Population Exchange exclusively in the light of the tragedy of the Asia Minor Hellenism and the efforts of the refugee resettlement in the new homeland. However, the 1923 Population Exchange has also another side, which is almost unknown in Greek historiography: the Muslims of the Greek ‘New Lands’ who immigrated to Turkey according to the terms of the Convention concerning the exchange of Greek and Turkish populations. Despite the condemnation to oblivion of the Population Exchange’s one side, Christian refugees and exchangeable Muslims met in the same place and lived together, intermittently, during the period 1914-1924 in the same settlement, in the same district, even in the same house. The aim of the paper is to survey the context and the characteristics of the symbiosis of these two population groups in the period from the first refugee settlements in the Greek state after the Balkan Wars until the final migration of Greece’s Muslims under the terms of the exchange in December 1924. Moreover, an effort will be made to determine whether the war conflicts, the conditions of nationalism’s exaltation, religious fanaticism, political disputes and the retaliation intentions by the victims of persecutions within the framework of minority policies formulated the terms of symbiosis between Christian refugees and Muslims. To what extent, that is, the above mentioned context of the years 1914-1924 created tensions and conflicts between Christian refugees and Muslims or, whether, in spite of the period’s circumstances, there was room for peaceful coexistence between the two sides of the Population Exchange.